Impact of Destination Brand Experience to Increase Destination Brand Loyalty - Tarigan, Miska Irani; Silalahi, Esli; Tinambunan, Anitha Paulina; Margery, Errie; Lusiah, Lusiah (Jurnal Aplikasi Manajemen, 2024)
Research related to brand loyalty is important, especially in the period following the Covid-19 pandemic. At that time, many tourism destinations and businesses were destroyed and tended to go bankrupt, so a strategy was needed to revive brand loyalty in tourist destinations in Indonesia which were famous as world tourist destinations. This research aims to provide a tourism marketing perspective with a destination brand experience. The brand experience felt by tourists is a series of efforts, activities or products received by tourists starting when tourists have a desire to travel. This research uses quantitative methods, data collection by questionnaire with a sample of tourists, the range of this research was conducted from January to May 2023 and by using a questionnaire on google form. The number of samples included in this study was 200 respondents, the sample determination was carried out by purposive sampling. Respondent data was analyzed by Structure Equation Model with Smart PLS 4.0. The results of this research found that destination brand experience has a positive effect on destination brand authenticity, destination brand satisfaction, and destination brand loyalty. Meanwhile, destination brand authenticity and destination brand satisfaction have a positive effect on destination brand loyalty. The results of the indirect influence show that destination brand authenticity and destination brand satisfaction mediate the influence of destination brand experience on destination brand loyalty.